2015
DOI: 10.1007/s00167-015-3847-6
|View full text |Cite
|
Sign up to set email alerts
|

Age does not affect the clinical and radiological outcomes after open-wedge high tibial osteotomy

Abstract: OWHTO using the rigid long plate was an effective procedure independent of patient's age. The results showed that age did not influence the clinical and radiological outcomes after OWHTO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 38 publications
4
69
1
1
Order By: Relevance
“…There are some reports that high tibial osteotomy has no effect on the ROM, and over 5 degrees of flexion contracture signifies contraindication for osteotomy. [1,7] Naudie et al [8] found that a preoperative ROM lower than 120 degrees associated with flexion contracture greater than 5 degrees was related to early failure (p-value 0.042). Flexion contracture as a contraindication is based on relatively poor results of small epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that high tibial osteotomy has no effect on the ROM, and over 5 degrees of flexion contracture signifies contraindication for osteotomy. [1,7] Naudie et al [8] found that a preoperative ROM lower than 120 degrees associated with flexion contracture greater than 5 degrees was related to early failure (p-value 0.042). Flexion contracture as a contraindication is based on relatively poor results of small epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…L ately, open-wedge high tibial osteotomy (OWHTO) has become a standard treatment option for medial compartment osteoarthritis (OA). 1,2 However, despite the favorable clinical outcomes associated with OWHTO, patellofemoral complications, including descent of the patellar height and patellofemoral malalignment, are usually reported after OWHTO. 3 Experimental biomechanical studies have established a correlation between OWHTO and a marked elevation in patellofemoral contact pressure, a phenomenon that exacerbates the risk of patellofemoral OA and anterior knee pain.…”
Section: See Related Article On Page 1703mentioning
confidence: 99%
“…No differences in outcomes were found in comparison to younger age groups. 34 So, age should be considered a very weak decision-making element to be taken into consideration.…”
Section: Age and Activitymentioning
confidence: 99%
“…However, newer outcome studies have proven that the procedure may be successful also in severe OA if the indication criteria are followed, and the technique is appropriate. 34,40,41…”
Section: Stage Of Osteoarthritismentioning
confidence: 99%